WATER QUALITY FOR IRRIGATION: HISTORICAL AND CURRENT SITUATION OF THE COLORADO RIVER - Maria Luján Masseroni; Carolina Manuela Aumassanne; Paolo Daniel Sartor; Carlos Damian Zamora; Dardo Roy Fontanella (Boletín Geográfico)
The quality of water for irrigations is conditioned by salt (amount and type) and the sediment it has. The characteristics of the water destined for irrigation influence the edaphic properties, the yield of the crops, the infrastructure of the irrigation systems and the durability of pressurized irrigation systems. The objective of this work was to compare the current data (2014-2017) and those from the historical series (1969-2007) of electrical conductivity (CE), total dissolved solids (TSD) and pH in the Multiple Use System of the Colorado River in 25 de Mayo (La Pampa). These parameters were periodically determined, on the matrix channel, which leads the water to the irrigated area of 25 de Mayo. The annual and inter annual behavior of the parameters in this period was analyzed regarding the monthly average values of the historical series that belong to the Ente Provincial del Río Colorado (Government of La Pampa). The analyzed results indicate that the monthly average of the EC and TSD of the last four years are higher than the monthly historical average. The pH was higher than the monthly historical average during 2014, except for the months of November and December. In 2015 and 2016, the registered values were lower than the historical ones. The changes of the analyzed results, specifically the salinity (EC and TSD), could be due mainly to the decrease in the flow that has been registered in the last years.